Comparison of the Application of the Problem Based Learning (Pbl) Model with the Project Based Learning (Pjbl) Model of Critical Thinking Skills and the Results of Writing Description Essays for Class V Students Cluster 1 Bajeng District, Gowa Regency: - - Fadilah, Nur; Munirah, Munirah; Tarman , Tarman (Jurnal Ilmiah Global Education, 2025)
This study was a Quasi Experimental study that aims (1) to describe students' critical thinking abilities through the Problem Based Learning (PBL) model of class V Elementary School Cluster 1, Bajeng District, Gowa Regency, (2) to describe students' descriptive writing abilities through the Project Based Learning (PjBL) model of class V Elementary School Cluster 1, Bajeng District, Gowa Regency, (3) to determine the differences between the PBL model and the PjBL model in improving critical thinking abilities and descriptive writing results of class V students of Elementary School Cluster 1, Bajeng District, Gowa Regency. The population in this study were students of grade V of SD Gugus 1 Bajeng District, Gowa Regency and the sample in this study were students of grade Va SD Negeri Panciro and grade Vb SD Negeri Panciro, each class consisting of 23 students. Data collection techniques used in this study were observation, learning outcome tests, and documentation. Data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis showed that critical thinking skills increased through the PBL learning model, this was supported by the results of the average posttest score reaching 87.65. While the ability to write descriptions also increased using the PjBL model, this was supported by the posttest score reaching 83.48. In the inferential results using the Independent Sample t-Test hypothesis test in the pretest experimental class 1 and 2 showed a probability value of 0.001 <significant level of 0.05 and Tcount of -11,532 and in the posttest experimental class 1 and 2 the probability value was 0.01 <significant level of 0.05 and Tcount -12,999 so it can be concluded that there is a significant difference between the PBL model and the PjBL model on critical thinking skills and descriptive writing results of class V students in Cluster 1, Bajeng District, Gowa Regency.